Cattle fattening: The Italian example - Vecchiettini M.; Giardini A. (Filière des viandes rouges dans les pays méditerranéens, 1998)
Beef cattle production systems are widely adopted on large stock farms (from 500 to 5,000 animals) in Northern Italy and are characterized by advanced technology and a strong entrepreneurial altitude. The animals used are predominantly young bulls (6-8 months of age). After being imported, they are reared in stables on slatted floors with tanks underneath for slurry collection. They are subjected to prophylaxis and consume a diet based on maize silage. All these technical aspects are investigated experimentally in order to find solutions capable of improving the overall efficiency of the system. In spite of the current difficulties in the beef sector due to a fall in consumption, the Italian fattening centres remain competitive due to the growing professionalism of he stock farmers.
Séminaire International sur la Filière des Viandes Rouges dans les Pays Méditerranéens, 20-23 Apr 1997, Tunis (Tunisia)